Mi hermana vive sobre la repisa de la chimenea - Pitcher, Annabel (Nuevos tiempos (Madrid, Spain), 2011)
With his family still grieving over his sister's death in a terrorist bombing seven years earlier, twelve-year-old Jamie is far more interested in his cat, Roger, his birthday Spiderman T-shirt, and keeping his new Muslim friend Sunya a secret from his father.